The Effect of Hybrid Working on Employee Productivity and Life Balance: A Human Resource Management Perspective - Berlianingsih Kusumawati (Maneggio, 2024)
The purpose of this study is to analyze how the implementation of a hybrid work model affects employee productivity and work-life balance in the context of human resource management. This study aims to explore the benefits and challenges experienced by employees who work with a hybrid system, as well as its impact on their well-being. To achieve this goal, the study uses the Systematic Literature Review (SLR) method by analyzing various related literature relevant to this topic. Based on the literature review conducted, it was found that hybrid working can increase productivity through flexibility of time and work space, but also has the potential to cause challenges in terms of work-life balance. The method used in this study is the Systematic Literature Review (SLR) approach, which is carried out by filtering scientific articles from various academic databases such as Google Scholar, JSTOR, and ScienceDirect. The results of this study indicate that hybrid working plays an important role in increasing job satisfaction and reducing work stress in most employees, although there are differences in its implementation between industrial sectors. Therefore, this study suggests the need for more flexible policies in the implementation of hybrid working in order to provide optimal impacts on employee productivity and work-life balance.